Thetha Nami ngithethe nawe (Let's Talk): a stepped-wedge cluster randomised trial of social mobilisation by peer navigators into community-based sexual health and HIV care, including pre-exposure prophylaxis (PrEP), to reduce sexually transmissible HIV amongst young people in rural KwaZulu-Natal, South Africa - Jacob Busang; Thembelihle Zuma; Carina Herbst; Nonhlanhla Okesola; Natsayi Chimbindi; Jaco Dreyer; Nelisiwe Mtshali; Theresa Smit; Samkelisiwe Ngubane; Siphesihle Hlongwane; Dumsani Gumede; Ashley Jalazi; et al. (BMC, 2023)
Abstract Background Antiretroviral therapy (ART) through universal test and treat (UTT) and HIV pre-exposure prophylaxis (PrEP) substantially reduces HIV-related mortality and incidence. Effective ART based prevention has not translated into population-level impact in southern Africa due to sub-optimal coverage among youth. We aim to investigate the effectiveness, implementation and cost effectiveness of peer-led social mobilisation into decentralised integrated HIV and sexual reproductive health (SRH) services amongst adolescents and young adults in KwaZulu-Natal (KZN). Methods We are conducting a type 1a hybrid effectiveness/implementation study, with a cluster randomized stepped-wedge trial (SWT) to assess effectiveness and a realist process evaluation to assess implementation outcomes. The SWT will be conducted in 40 clusters in rural KZN over 45 months. Clusters will be randomly allocated to receive the intervention in period 1 (early) or period 2 (delayed). 1) Intervention arm: Resident peer navigators in each cluster will approach young men and women aged 15-30 years living in their cluster to conduct health, social and educational needs assessment and tailor psychosocial support and health promotion, peer mentorship, and facilitate referrals into nurse led mobile clinics that visit each cluster regularly to deliver integrated SRH and differentiated HIV prevention (HIV testing, UTT for those positive, and PrEP for those eligible and negative). Standard of Care is UTT and PrEP delivered to 15-30 year olds from control clusters through primary health clinics. There are 3 co-primary outcomes measured amongst cross sectional surveys of 15-30 year olds: 1) effectiveness of the intervention in reducing the prevalence of sexually transmissible HIV; 2) uptake of universal risk informed HIV prevention intervention; 3) cost of transmissible HIV infection averted. We will use a realist process evaluation to interrogate the extent to which the intervention components support demand, uptake, and retention in risk-differentiated biomedical HIV prevention. Discussion The findings of this trial will be used by policy makers to optimize delivery of universal differentiated HIV prevention, including HIV pre-exposure prophylaxis through peer-led mobilisation into community-based integrated adolescent and youth friendly HIV and sexual and reproductive health care. Trial registration ClinicalTrials.gov Identifier-NCT05405582. Registered: 6th June 2022.